2004
DOI: 10.1099/mic.0.26823-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of pcpS, encoding the multifunctional phosphopantetheinyl transferase of Pseudomonas aeruginosa

Abstract: Fatty acid synthases (primary metabolism), non-ribosomal peptide synthases and polyketide synthases (secondary metabolism) contain phosphopantetheinyl (Ppant)-dependent carrier proteins that must be made functionally active by transfer of the 49-Ppant moiety from coenzyme A. These reactions are usually catalysed by dedicated Ppant transferases. Although rich in Ppant-dependent carrier proteins, it was previously shown that Pseudomonas aeruginosa possesses only one Ppant transferase, encoded by pcpS, which func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…The domain boundaries (1707-1919 aa) for the PPTase domain were initially determined by sequence alignment with type II PPTases [19,20]. The purified PPTase domain protein contains 213 residues and is referred as PPTase1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The domain boundaries (1707-1919 aa) for the PPTase domain were initially determined by sequence alignment with type II PPTases [19,20]. The purified PPTase domain protein contains 213 residues and is referred as PPTase1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, PPTase is essential for the production of mupirocin in P. fluorescens (Shields et al 2010), erythromycin in Saccharopolyspora erythraea (Weissman et al 2004), fatty acid in E. coli strain O157:H7 (Lay and Lay and Cronan 2006), both fatty acid and siderophore in P. aeruginosa (Barekzi et al 2004) and for the biosynthesis of virulence factors in Mycobacterium (Chalut et al 2006). Identification of the role of ZmsO in zeamines production adds a new member to the list of PPTases which are associated with the biosynthesis of secondary metabolites with biological significances.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that Sppt and Hppt phosphopantetheinylate ACPs involved in primary metabolism [18,22]; PPT Ns phosphopantetheinylates ACPs and PCPs involved in secondary metabolism [4]; PcpS phosphopantetheinylates ACPs and PCPs involved in both primary metabolism and secondary metabolism [1]. In this study, we characterized the specificities of Hppt and Sppt and the effects of their N/C terminus to the activities.…”
Section: Introductionmentioning
confidence: 97%
“…Few bacteria contain only one group II PPTase, which should be involved in both primary metabolism and secondary metabolism in the absence of group I PPTase, such as PcpS in Pseudomonas aeruginosa [1], PPT Ns in Nodularia spumigena NSOR10 [4], Sppt in Synechocystis sp. PCC6803 [18], and Hppt in Haemophilus influenza.…”
Section: Introductionmentioning
confidence: 99%